IDENTIFIKASI KANDUNGAN ZAT MAKANAN PADA BIJI BUAH DI PASAR BANDAR LAMPUNG - Wibowo, Ayyub; Fathul, Farida (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
The purpose of this study was to determine the water content, protein, and fat in the avocado seed jackfruit and durian obtained from traditional markets in Bandar Lampung. Materials used in this research are the seeds of avocado, jackfruit seeds, and seeds of durian. The material obtained from the three traditional markets, namely Bandar Lampung Bambu Kuning, Markets Teluk, and Market Way Halim. This research was conducted using a survey method with the sampling design. Samples were taken three replications from each market using purposive random sampling. The results showed that: (1) the moisture content of 81.28% jackfruit seeds, avocado seed 60.16%, and 45.95% durian seeds (2) The lipid content of crude oil in the avocado seed 11: 40%, 10 durian seeds, 98%, and jackfruit seeds 10: 25% (3) the protein content in seeds 11.70% jackfruit, durian 6: 56% of fruit seeds, and avocado seed 6: 52%. Keywords: Avocado Seeds,Seeds of Jackfruit, Durian Fruit Seeds